The Inability of podocytes to proliferate: cause, consequences, and origin - Kriz, Wilhelm (The anatomical record, 2020)
This study presents a theoretical analysis of the problems related to the inability of podocytes to proliferate. The basis of these problems is the very high rate of glomerular filtration. Podocytes do not in general die by apoptosis or necrosis but are lost by detachment from the glomerular basement membrane (GBM) as viable cells.
First published: 12 October 2019
Gesehen am 20.01.2021